Role of cardiopulmonary interactions in development of ventilator-induced lung injury—Experimental evidence and clinical Implications - Shah, Neel; Katira, Bhushan H. (Frontiers in Physiology, 2023)
Ventilator-induced lung injury (VILI) impacts outcomes in ARDS and optimization of ventilatory strategies improves survival. Decades of research has identified various mechanisms of VILI, largely focusing on airspace forces of plateau pressure, tidal volume and driving pressure. Experimental evidence indicates the role of adverse cardiopulmonary interaction during mechanical ventilation, contributing to VILI genesis mostly by modulating pulmonary vascular dynamics. Under passive mechanical ventilation, high transpulmonary pressure increases afterload on right heart while high pleural pressure reduces the RV preload. Together, they can result in swings of pulmonary vascular flow and pressure. Altered vascular flow and pressure result in increased vascular shearing and wall tension, in turn causing direct microvascular injury accompanied with permeability to water, proteins and cells.Moreover, abrupt decreases in airway pressure, may result in sudden overperfusion of the lung and result in similar microvascular injury, especially when the endothelium is stretched or primed at high positive end-expiratory pressure. Microvascular injury is universal in VILI models and presumed in the diagnosis of ARDS; preventing such microvascular injury can reduce VILI and impact outcomes in ARDS.Consequently, developing cardiovascular targets to reduce macro and microvascular stressors in the pulmonary circulation can potentially reduce VILI. This paper reviews the role of cardiopulmonary interaction in VILI genesis.